Trends in Shared Decision-Making Studies From 2009 to 2018: A Bibliometric Analysis - Cuncun Lu; Cuncun Lu; Xiuxia Li; Xiuxia Li; Kehu Yang; Kehu Yang (Frontiers Media S.A., 2019)
Background: To systematically analyze the global development trends and research focuses of shared decision-making (SDM) studies as a reference for researchers.Methods: We conducted a systematic search of the Web of Science (WoS) Core Collection on April 17, 2019, to retrieve studies related to SDM published from 2009 to 2018. VOSviewer (1.6.10), CiteSpace (5.4.R1) and Excel 2016 were used to analyze key features of SDM studies, including annual output, countries/regions, organizations, journals, authors, references, research hot-spots, and frontiers.Results: Up to April 17, 2019, a total of 6,629 studies on SDM were identified as published between 2009 and 2018. The United States participated in the most studies (n = 3,118), with the University of California-San Francisco ranking first (n = 183). Patient Education and Counseling [impact factor (IF) 2017 = 2.785] published the most studies (n = 257). Legare F participated in the most studies (n = 101), and the paper "Charles C, 1997, Soc Sci Med, V44, P681" occupied the highest co-citation (n = 657) position. The research hotspots and frontiers included "Informed consent," "Surgery," "Depression," "Older adult," and "Patient-centered care."Conclusion: The number of studies concerning SDM has continued to increase since 2009, with the United States leading the field. The landscape of the basis of SDM included mainly concept, practice framework and effect assessment of SDM. "Informed consent," "Surgery," "Depression," "Older adult," and "Patient-centered care" reflected the latest research focuses, and should receive more attention.